THE EFFECT OF MANURE AND NITROGEN FERTILIZER COMBINATION ON THE GROWTH AND YIELD OF SPRING ONION IN PEAT SOIL - Paulus, Sardi; Anggorowati, Dini; Hariyanti, Agus (Jurnal Sains Mahasiswa Pertanian, 2019)
This study aimed to find the best combination of manure and Urea fertilizer dosage on the growth and yield of spring onions on peatsoil. This research took place from February 7 - April 8, 2019 and was located on Jalan Parit Haji Muksin II Kubu Raya. This study used an experimental method Completely Randomized Design, consisting of types of manure combined with N fertilizer consisting of 6 levels of treatment, encoded A (chicken manure + Urea 100 kg / ha), B (chicken manure + Urea 200 kg / ha), C (chicken manure + Urea 300 kg / ha), D (cow manure + Urea 100 kg / ha), E (cow manure + Urea 200 kg / ha), F (cow manure + Urea 300 kg / ha). Each treatment were repeated 4 times so that there were 24 expermental units whith Â 4 samples per replication so that the total of plant number were 96 plants. The observation variables in this study were plant height, number of leaves, number of tillers, root volume, leaf dry weight, root dry weight, fresh leaf weight. Observations were also made on the environmental conditions of the study, such as rainfall, air temperature, humidity. The results showed that the administration of manure and N fertilizer with a dose of chicken manure 20 tons / ha and 100 kg / ha Urea was an effective dose on the average of each observation variable of leeks on peat soil.Â Keywords: spring onion, manure, N fertilizer and peat.